1999 IEEE International Conference on Acoustics, Speech, and Signal Processing. Proceedings. ICASSP99 (Cat. No.99CH36258) 1999
DOI: 10.1109/icassp.1999.759860
|View full text |Cite
|
Sign up to set email alerts
|

Plucked-string synthesis algorithms with tension modulation nonlinearity

Abstract: Digital waveguide modeling of a nonlinear vibrating string is investigated when the nonlinearity is essentially caused by tension modulation. We derive synthesis models where the nonlinearity is implemented with a time-varying fractional delay filter. Also, conversion from a dual-delay-line physical model into a single-delay-loop model is explained. Realistic synthetic tones with nonlinear effects are obtained by introducing minor amendments to a linear string synthesis algorithm. It is shown how synthetic plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…This work was supported by the GETA Graduate School, Helsinki University of Technology, Jenny ja Antti Wihurin rahasto (the Foundation of Jenny and Antti Wihuri), and the Academy of Finland. Preliminary results of this study were reported in [1]. The associate editor coordinating the review of this manuscript and approving it for publication was Dr.-Ing.…”
Section: Introductionmentioning
confidence: 92%
“…This work was supported by the GETA Graduate School, Helsinki University of Technology, Jenny ja Antti Wihurin rahasto (the Foundation of Jenny and Antti Wihuri), and the Academy of Finland. Preliminary results of this study were reported in [1]. The associate editor coordinating the review of this manuscript and approving it for publication was Dr.-Ing.…”
Section: Introductionmentioning
confidence: 92%
“…Perhaps the simplest example of nonlinear behavior in the shell model (5) is the pitch glide, a common feature across many percussive instruments. The modeling of pitch glides, for synthesis, has been approached in the case of strings and membranes through a variety of methods [11], [29], [30]. Usually the pitch glide is downward, from the moment of impact excitation, reflecting stiffening behavior of the medium at higher vibration amplitudes (though upward pitch glides are also possible [4]).…”
Section: Pitch Glidesmentioning
confidence: 99%
“…A different approach to dynamic tension variations in string models has been recently proposed by Välimäki et al [11], [21]. They recast the resampling process induced by tension modulation into delay length modulation of a FIR line controlled by the buffer content.…”
Section: Fig 11mentioning
confidence: 99%